2015
DOI: 10.4097/kjae.2015.68.2.141
|View full text |Cite
|
Sign up to set email alerts
|

Epidural anesthesia for pilonidal sinus surgery: ropivacaine versus levobupivacaine

Abstract: BackgroundEpidural anesthesia is one of the best options for lower abdominal and lower limb surgery. However, there have been insufficient reports regarding the use of epidural anesthesia for pilonidal sinus surgery. The present study was performed to compare the clinical profiles of epidural block performed with 0.75% levobupivacaine and 0.75% ropivacaine in this procedure.MethodsThirty patients undergoing pilonidal sinus surgery were randomly allocated into two groups: one group received levobupivacaine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
1
2
0
2
Order By: Relevance
“…Results similar to our study were also found by Zeynep Nur Orhon et.al. In 2015 9 As in our study they also found it easy for Ropivacaine group to be mobilised early due to lesser motor block compared to Levo-Bupivacaine group though the Bromage scale scores were statistically not significant.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Results similar to our study were also found by Zeynep Nur Orhon et.al. In 2015 9 As in our study they also found it easy for Ropivacaine group to be mobilised early due to lesser motor block compared to Levo-Bupivacaine group though the Bromage scale scores were statistically not significant.…”
Section: Discussionsupporting
confidence: 47%
“…A higher score indicates greater pain intensity. Based on the distribution of pain VAS scores in postsurgical patients (knee replacement, hysterectomy, or laparoscopic myomectomy) who described their postoperative pain intensity as none, mild, moderate, or severe, the following cut points on the pain VAS have been recommended: no pain (0-1), mild pain (2-4), moderate pain (5-7), and severe pain (8)(9)(10). Fig No. 1.…”
Section: ) Visual Analog Saclementioning
confidence: 99%
“…[1] A recent study has shown that epidural anesthesia is a suitable anesthetic technique for pilonidal sinus surgery with respect to hemodynamic stability, onset time of analgesia, duration of sensorial block, lack of motor block, side effects, and satisfaction of surgeon and patient. [2] Subdural block occurring as a result of local anesthetic spread in the subdural space without dural puncture after epidural block is a rare complication, and its symptoms show similarity with high subarachnoid block. [3] Diagnosing this complication may be difficult because of diverse symptoms and findings.…”
Section: Introductionmentioning
confidence: 99%
“…Başlaması genellikle 12-72 saat sonradır, ancak daha erken de ortaya çıkabilir. 7,8,9,10,11,12,13,14 Dural defektten kaçış sonucu oluştuğuna inanılır. Kan damarları üzerinde yüksek çekilme ağrıya katkıda bulunur.…”
unclassified
“…Oluşma olasılığını arttıran diğer faktörler ise genç yaş, dişi cinsiyet ve gebeliktir. 7,8,9,10,11,12,13,14 Bu nedenle yüksek insidans epidural iğne ile duranın yanlışlıkla delindiği obstetrik hastalarda beklenmelidir (%20-50). Sezaryen nedeniyle spinal anestezi yapılanlarda %3-4 oranında izlenmektedir.…”
unclassified